2009
DOI: 10.1016/j.cognition.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to syntax in visual cortex

Abstract: One of the most intriguing findings on language comprehension is that violations of syntactic predictions can affect event-related potentials as early as 120 ms, in the same time-window as early sensory processing. This effect, the so-called early left-anterior negativity (ELAN), has been argued to reflect word category access and initial syntactic structure building (Friederici, 2002). In two experiments, we used magnetoencephalography to investigate whether (a) rapid word category identification relies on ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(179 citation statements)
references
References 57 publications
14
164
1
Order By: Relevance
“…Psycholinguistic research has also shown that closed class morphemes have a special status in language processing (e.g., Bradley, 1983). Consistent with the hypothesis that the M100 category effect is dependant on the presence of closed class morphemes, in Dikker et al (2009) we only found an M100 effect when the category of the unexpected item was saliently marked by a closed-class morpheme.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Psycholinguistic research has also shown that closed class morphemes have a special status in language processing (e.g., Bradley, 1983). Consistent with the hypothesis that the M100 category effect is dependant on the presence of closed class morphemes, in Dikker et al (2009) we only found an M100 effect when the category of the unexpected item was saliently marked by a closed-class morpheme.…”
Section: Introductionsupporting
confidence: 89%
“…Typical vs. Neutral) within-subjects ANOVA on the mean amplitude of a 15ms interval centered around the average M100 peak for each condition and subject, as in Dikker et al (2009). Post-hoc ttests were used to examine effects within each noun type.…”
Section: Resultsmentioning
confidence: 99%
“…For example, listeners are more likely to direct their eye-gaze to a picture of an edible object (e.g., a cake) when they hear the beginning of an utterance like 'The boy will eat…' compared to a neutral utterance such as 'The boy will move…' (Altmann & Kamide, 1999). Further, much evidence has suggested that comprehenders compute rich expectations about upcoming inputs at multiple levels of representation (syntactic: Ilkin & Sturt, 2011;Lau, Stroud, Plesch, & Phillips, 2006;Levy, Fedorenko, Breen, & Gibson, 2012;Omaki et al, 2015;Staub & Clifton, 2006;Wicha et al, 2004;Van Berkum et al, 2005;Yoshida, Dickey, & Sturt, 2013;lexico-semantic: Federmeier & Kutas, 1999;Kutas & Hillyard, 1984;Otten & Van Berkum, 2008;Szewczyk & Schriefers, 2013; phonological and orthographic: Delong et al, 2005;Dikker, Rabagliati, Farmer, & Pylkkanen, 2010;Dikker, Rabagliati, & Pylkkänen, 2009;Farmer, Yan, Bicknell, & Tanenhaus, 2015;Kim & Lai, 2012;Laszlo & Federmeier, 2009). Here, we operationally define 'prediction' as the pre-activation of stored representations before the bottom-up input is encountered, and we will make no a priori assumptions regarding the nature of the mechanisms involved (e.g., whether they are automatic or controlled).…”
Section: Prediction In Language Comprehensionmentioning
confidence: 99%
“…One alternative interpretation argues that these early components instead index mismatches between predicted sensory input and actual sensory input (e.g., the wordform by is visually surprising in a context in which a noun was expected, because this wordform is only used as a preposition, Dikker, Rabagliati, Farmer, & Pylkkänen, 2010;Dikker, Rabagliati, & Pylkkänen, 2009;Kim & Lai, 2012); under this account, the ERP response to by does not reflect combinatorial syntactic processing, but a sensory prediction error. A second, more deflationary account, has argued that early ERP responses to ungrammatical words might also result from artefacts caused by how ERP data are baseline corrected (Steinhauer & Drury, 2012).…”
Section: The Potential For False Positives In the Breaking Cfs Paradigmmentioning
confidence: 99%